2017
DOI: 10.1186/s12906-016-1498-x
|View full text |Cite
|
Sign up to set email alerts
|

Edible bird’s nest modulate intracellular molecular pathways of influenza A virus infected cells

Abstract: BackgroundEdible Bird’s Nest (EBN) as a popular traditional Chinese medicine is believed to have health enhancing and antiviral activities against influenza A virus (IAV); however, the molecular mechanism behind therapeutic effects of EBN is not well characterized.MethodsIn this study, EBNs that underwent different enzymatic preparation were tested against IAV infected cells. 50% cytotoxic concentration (CC50) and 50% inhibitory concentration (IC50) of the EBNs against IAV strain A/Puerto Rico/8/1934(H1N1) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…Haghani et al studied the "in vitro and in vivo mechanism of immunomodulatory and antiviral activity of EBN against influenza A virus infection [9] . Immunomodulation via cytokine induction due to EBN has been reported [10] . Haghani et al [11] commented on "the potential of EBNs as supplementary medication or alternative to antiviral agents to inhibit influenza infections".…”
Section: Chinese Medicine For Emerging Influenzamentioning
confidence: 99%
“…Haghani et al studied the "in vitro and in vivo mechanism of immunomodulatory and antiviral activity of EBN against influenza A virus infection [9] . Immunomodulation via cytokine induction due to EBN has been reported [10] . Haghani et al [11] commented on "the potential of EBNs as supplementary medication or alternative to antiviral agents to inhibit influenza infections".…”
Section: Chinese Medicine For Emerging Influenzamentioning
confidence: 99%
“…Edible bird's nest (EBN; known as Yanwo in Chinese), which comes from swiftlets belonging to the family Apodidae and the genus Aerodramus, has multiple nutritional and pharmaceutical benefits, such as pro-conception effects, neuroprotective effects and bone loss improvement (Matsukawa et al, 2011;Careena et al, 2018;Albishtue et al, 2019;Hou et al, 2019). Additionally, some studies have shown that EBN with antiviral activities can regulate the expression of some immune cytokines involved in influenza A virus infection, such as tumour necrosis factor α (TNF-α), interferon (IFN)-γ, interleukin (IL)-1β, IL-6, IL-10 and chemokine (C-C motif) ligand (CCL) 2 (Haghani et al, 2016;Haghani et al, 2017). Several pro-inflammatory cytokines (e.g., IL-1β, IL-6 and TNF-α) that can induce Th17 cell polarization have key roles in the pathogenesis of UC (Acosta-Rodriguez et al, 2007;Gálvez, 2014;Lee et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, there has been a growing interest in the use of natural products for their medicinal values (Kamil et al, 2018;Hamid et al, 2020;Kamil et al, 2020;Prom-In et al, 2020). EBN, is an emerging food product with known anti-viral effects, especially against Influenza A virus (IAV) (Guo et al, 2006;Haghani et al, 2016;Haghani et al, 2017), the most common cause of the global pandemic. EBN significantly reduced viral titer, viral-induced hemagglutination (Haghani et al, 2017), virus-binding activity (Guo et al, 2006), and virus-induced endocytosis and autophagosomes (Haghani et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…EBN, is an emerging food product with known anti-viral effects, especially against Influenza A virus (IAV) (Guo et al, 2006;Haghani et al, 2016;Haghani et al, 2017), the most common cause of the global pandemic. EBN significantly reduced viral titer, viral-induced hemagglutination (Haghani et al, 2017), virus-binding activity (Guo et al, 2006), and virus-induced endocytosis and autophagosomes (Haghani et al, 2017). In addition to anti-viral, EBN also demonstrated antiinflammatory (Vimala et al, 2012), anti-oxidant (Yew et al, 2014), and immunomodulatory properties (Haghani et al, 2016), indicating its potential as an all-around prophylactic or therapeutic option for influenza, SARS-CoV-2 and its associated complications, such as cytokine storm.…”
Section: Introductionmentioning
confidence: 99%